2023
DOI: 10.1146/annurev-neuro-083122-025325
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Interneurons: Diversity and Connectivity in Motor Control

Abstract: The spinal cord is home to the intrinsic networks for locomotion. An animal in which the spinal cord has been fully severed from the brain can still produce rhythmic, patterned locomotor movements as long as some excitatory drive is provided, such as physical, pharmacological, or electrical stimuli. Yet it remains a challenge to define the underlying circuitry that produces these movements because the spinal cord contains a wide variety of neuron classes whose patterns of interconnectivity are still poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…8A, bottom ). In our model, we include the two specific types of V2a neurons and single generic sources of recurrent and reciprocal inhibition, each of which has the potential to form connections with the other types (Sengupta and Bagnall, 2023). We do not include conserved sources of commissural excitation here (e.g., V0v and V3 neurons), but these will be important to include in any future models exploring intersegmental coordination and signal amplification (Bohm et al, 2022; Kawano et al, 2022; Wiggin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…8A, bottom ). In our model, we include the two specific types of V2a neurons and single generic sources of recurrent and reciprocal inhibition, each of which has the potential to form connections with the other types (Sengupta and Bagnall, 2023). We do not include conserved sources of commissural excitation here (e.g., V0v and V3 neurons), but these will be important to include in any future models exploring intersegmental coordination and signal amplification (Bohm et al, 2022; Kawano et al, 2022; Wiggin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature, developed over a century, provides a wealth of detail on spinal cord anatomy and cell type distributions (Roome and Levine, 2023; Sengupta and Bagnall, 2023). Emerging technologies for large-scale, chronic recording and stimulation of spinal populations (Berg et al, 2009; Metuh et al, 2024; Wu et al, 2023), as well as the advancements in approaches to monitor and manipulate the well-defined spinal inputs (i.e., tactile, proprioceptive, nociceptive neurons) and outputs (i.e., motorneurons (Chung et al, 2023)) are rapidly being realized.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we will focus on the premotor INs contained in motor circuits and how they react after different kinds of TSCI. For a broader information about the spinal circuitry responsible for the locomotion in the ventral spinal cord and central pattern generators, the authors strongly recommend reviewing the indicated publications [23][24][25][26][27][28]. neurons (MNs), which receive inputs from supraspinal centers and sensory afferents (in a direct or indirect way) and send their output to muscles and premotor interneurons (INs).…”
Section: Introductionmentioning
confidence: 99%